Branching Out: Mobilising Parents’ Assets to Support Children’s Learning in Pre-Primary Schools - Johnson Kojo; Jacob Seni; Placidius Ndibalema (Journal of Innovation and Community Engagement, 2026)
Mobilising parents’ existing assets is increasingly regarded as an important strategy to improve early childhood education in resource-limited contexts. This pilot study utilised Participatory Action Research (PAR) in conjunction with Ward’s (2019) Asset-Based Community Development (ABCD) logical model in two government pre-primary schools in the Nzega district, Tanzania. Thirteen parent connectors received training and support to identify community assets, prioritise actionable steps, and implement peer-led training and volunteer programs. Thematic analysis of meetings, interviews, and observations indicated a transition from a deficit perspective of parents to an acknowledgement of their social and human capital as significant assets. Data from 160 parents, collected before and after the study, showed a significant improvement (p < 0.001) in parents’ competencies in home learning support, homework assistance, meeting attendance, and school volunteering. In three months, parent volunteers made 54 instructional aids in the intervention schools. This pilot study shows that an ABCD logical model may be effective, acceptable, and a promising start toward increasing parents' engagement in their children's pre-primary education in Tanzania.